Kesejahteraan Ekonomi Masyarakat dalam Program Makan Bergizi Gratis Melalui Analisis Teori Utilitarianisme Jeremy Bentham - Annisa Luluk Firdausie (Institut Nalanda, 2026)
This article aims to explain how the Indonesian government under the Prabowo–Gibran administration implements the Free Nutritious Meals (MBG) policy to promote community economic welfare from the perspective of Jeremy Bentham's utilitarianism. This study employs a qualitative method with a literature study analytical approach, seeking an in-depth understanding of the MBG program through comprehensive analysis of relevant academic sources and Jeremy Bentham's theory of utilitarianism. The findings indicate that the MBG program is consistent with Bentham's principle of